Investigating the Effect of Enquiry-Based Learning Approach in Science on Junior High School 2 Students in Paradise International School (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose for this research was to compare any differences between enquiry-based learning methods and the traditional methods of teaching science in JHS 2. The study employed the Quasi-experimental research and action research methods under both quantitative and qualitative paradigms of research design. The selection of the school was done through purposive sampling method. The research participants were JHS 2 students (N = 30) in two science classes at the research school. The traditional class was the control group. Two data collection instruments - Science Knowledge Assessment and Engagement checklist were used. It was found out that enquiry based teaching allow students to engage, discover, draw conclusions and report their findings increased their abilities to reason and problem solving. It was recommended that discussion in science should be the focus of enquiry based learning.